Influence of third-order susceptibility on electromagnetically induced grating in a three-level V-type atomic system - Nguyen Huy, Bang; Dinh Xuan, Khoa; Luong Thi Yen, Nga; Ho Hai, Quang; Nguyen, Van Ai; Le Van, Doai (Communications in Physics, 2024)
In addition to the suppressed absorption in the atomic resonance region, an electromagnetically induced transparency (EIT) medium also possess giant nonlinear dispersion which significantly affects the optical properties of the medium. In this work, we study the influence of third-order nonlinear susceptibility on electromagnetically induced grating (EIG) in a three-level V-type atomic medium. By applying stationary perturbation theory to the density matrix equations describing the time evolution of the quantum states of the system, we have found density matrix solutions to the third-order perturbation corresponding to the third-order susceptibility, and found the transmission function for the probe light. Using the Fourier transform of the transmission function, we can obtain the intensity distribution function of the EIG diffraction spectrum as a function of laser parameters and the atomic medium. To see the influence of third-order susceptibility on EIG diffraction spectrum, we have simulated EIG spectra in two cases with and without third-order susceptibility. We found that the first-order diffraction efficiency was significantly enhanced when third-order susceptibility was introduced.